Experimental investigation of flow and convective heat transfer on a high-Prandtl-number fluid through the nuclear reactor pebble bed core. (25th December 2018) - Liu, Limin; Zhang, Dalin; Li, Linfeng; Yang, Yicheng; Wang, Chenglong; Qiu, Suizheng; Su, G.H.
Highlights: A pebble bed test facility with internal heat source is setup for FHRs. High-Pr Dowtherm A at low temperature simulates high-temperature FLiBe. Flow regime transition criteria is setup. Flow and convective heat transfer correlations are obtained for FLiBe in FHRs. Abstract: For Fluoride-salt-cooled High-temperature Reactors (FHRs), a pebble bed experimental facility with internal heat generation is set up, using the Dowtherm A as the simulant fluid. Dowtherm A can match the Prandtl number of FLiBe of 520–700 °C at a low temperature range of 45–105 °C. The effects of inlet temperatures, porosity and mass flow rate are investigated on the flow and convective heat transfer characteristics. A criterion is determined for the flow regime transition from the transitional to turbulent flow. The existing correlations are unable to predict the Blake-type friction factor in the transitional flow and show mixed performance in the turbulent flow. The present empirical correlations generally underestimate the convective heat transfer coefficients of the high-Prandtl-number fluid in the pebble bed. New correlations are proposed for predicting the flow and convective heat transfer coefficients with Prandtl number at 14–19 and Reynolds number at 90–2500.